The utility of FDG-PET/CT imaging in the evaluation of multicentric reticulohistiocytosis: A case report. Issue 33 (August 2018) - Asano, Tomoyuki; Suzutani, Ken; Watanabe, Aya; Honda, Aki; Mori, Natsumi; Yashiro, Makiko; Sato, Shuzo; Kobayashi, Hiroko; Watanabe, Hiroshi; Hazama, Momoko; Kanno, Takashi; Suzuki, Eiji; et al.
Abstract: Introduction: Multicentric reticulohistiocytosis (MRH) is a rare histiocytic disorder that involves the skin, joints, and visceral organs. Case presentation: We report a 67-year-old woman with MRH who presented with a 2-years history of polyarthralgia and skin nodules. Her symptoms were an inflammatory polyarthropathy with punched-out lesions of the distal interphalangeal (DIP) joints of both hands. Doppler ultrasonography of the hands showed large bone erosions with power Doppler signals in the DIP joints. 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) demonstrated increased FDG uptake in cutaneous papules surrounding the affected joints, suggesting an inflammatory process. There was no evidence of malignancy. Biopsy samples of skin nodules exhibited dermal infiltration with CD68-positive histiocytes and multinucleated giant cells. The patient was diagnosed with MRH and treated with combination therapy comprising a steroid (prednisolone), tacrolimus, methotrexate, and infliximab, which resulted in clinical improvement. Following infliximab treatment, there was a significant decrease in a bone resorption marker (tartrate-resistant acid phosphatase 5b: TRACP-5b), suggesting that tumor necrosis factor-α targeting therapy may inhibit osteoclast formation and resorption activity in patients with MRH. Conclusion: MRH is a progressive destructive arthritic condition, and early diagnostic and therapeutic strategies are necessary to improve the outcome. FDG-PET/CT and joint ultrasonography might be noninvasive imaging modalities that could help diagnose MRH.